The fall of perseverance and rise of indomitable spirit within taekwon-do during COVID-19 - Johnson, J. A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. Taekwon-Do, a South Korean martial art and combat sport teaches hundreds of physical skills through a stratified curriculum. The highest learning objectives of Taekwon-Do are, however, its five tenets (courtesy, integrity, perseverance, self-control, and indomitable spirit). Unlike the physical aspects of Taekwon-Do practice, there are no direct assessment tools that can determine if a student has acquired and utilized the tenets. The challenges of the COVID-19 pandemic may provide a unique opportunity to assess the acquisition of some of the tenets of Taekwon-Do. Problem and Aim. This study aims to provide an indirect method of assessing students` adoption of some of Taekwon-Do`s tenets by understanding how these ideals may enable Taekwon-Do practitioners to overcome physical and emotional challenges in their daily lives. Methods. The research methodology utilizes an autoethnographic research design that correlates the author`s application of the tenets of Taekwon-Do to his mental and spiritual health successes after suffering through the COVID-19 pandemic and life-altering physical injuries. Results. COVID-19, like the author`s injuries, provides an indirect and qualitative assessment opportunity for two tenets of Taek- wondo (perseverance and indomitable spirit). Conclusion. While indirect assessment is a viable and established pedagogical means of assessment, quantitative measurement tools may be more persuasive to prove the effectiveness of the tenets of Taekwon-Do.